Investigation of Internal Gas Leakage on the Gate Valve using Acoustic Signal - Mustapha, Ismail; Md Saad, Mohamad Hanif; Nuawi, Mohd Zaki; Sani, Suhairy; Mohd, Shukri; Mohamad, Siti Fatahiyah; Omar, Ratna Suffhiyanni (International Journal of Integrated Engineering, 2022)
The gate valve is primarily used for starting/stopping the flow of fluids. It is suitable for most fluids such as water and chemicals as well as air, steam and gas in petrochemical and refinery plants that require high temperature and low pressure. The aim of this study is to define the frequency domain using AE signals, such as RMS and ASL, to determine the internal gas leakage. The conducted experiment employed a 4-inch diameter gate valve installed in the middle of the pipe length. To simulate industrial applications, the AE signals were observed at low-frequency (between 18.6 kHz to 19.5 kHz), with inlet pressures between 100 to 800 kPa and leakage rates between 0.5 percent to 2 percent. The frequency domain between 18.6 to 19.5 kHz and the inlet pressure of 100 to 800 kPa were displayed as the Root Mean Square (RMS) and Average Signal Limit (ASL). The pressure difference between the inlet and outlet influences the AE signal. The frequency spectrum can be correlated with the pressure leakage, thus providing leakage conditions. Therefore, the obtained results can be employed in industrial applications.